2012
DOI: 10.1182/blood-2011-09-382473
|View full text |Cite
|
Sign up to set email alerts
|

Mature erythrocyte membrane homeostasis is compromised by loss of the GATA1-FOG1 interaction

Abstract: GATA1 plays essential roles in erythroid gene expression. The N-terminal finger of GATA1 (GATA1-Nf) is important for association with FOG1. Substitution mutations in GATA1-Nf, such as GATA1 V205M that diminish the GATA1-FOG1 association, have been identified in human thrombocytopenia and anemia cases. A mouse model of human thrombocytopenia has been established using a transgenic complementation rescue approach; GATA1-deficient mice were successfully rescued from embryonic lethality by excess expression of GAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…Several families with inherited anemia and thrombocytopenia have been reported to harbor GATA1 mutations lacking the potential to interact with FOG1 (43). In this regard, we have conducted transgenic complementation rescue analyses of GATA1-deficient mice utilizing the GATA1 V205G (G1 V205G ) mutant that shows reduced FOG1-interacting activity and found that the rescued mice are prone to suffer from severe spherocytic hemolysis and thrombocytopenia (29,32). In the rescued mice, expression of GATA1 target genes related to the red cell membrane structure is markedly reduced, while expression of the GATA1 target genes related to the erythroid differentiation is relatively preserved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several families with inherited anemia and thrombocytopenia have been reported to harbor GATA1 mutations lacking the potential to interact with FOG1 (43). In this regard, we have conducted transgenic complementation rescue analyses of GATA1-deficient mice utilizing the GATA1 V205G (G1 V205G ) mutant that shows reduced FOG1-interacting activity and found that the rescued mice are prone to suffer from severe spherocytic hemolysis and thrombocytopenia (29,32). In the rescued mice, expression of GATA1 target genes related to the red cell membrane structure is markedly reduced, while expression of the GATA1 target genes related to the erythroid differentiation is relatively preserved.…”
Section: Discussionmentioning
confidence: 99%
“…Sample preparations were performed as previously described with minor modifications (29). Briefly, 1 ϫ 10 7 liver cells of E12.5 mouse embryos and 1 ϫ 10 7 cells of MEL cell clones that express biotinylated GATA1 proteins were cross-linked with 1% and 0.4% formaldehyde for 10 min, respectively, and neutralized with glycine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatin Immunoprecipitation (ChIP) Assay-Chromatin fixation and purification procedures were performed as described previously (24) with the exception that mouse erythroleukemia (MEL) cells were used. MEL cells were cultured in a same manner as the QT6 cells.…”
Section: Methodsmentioning
confidence: 99%
“…Erythrocyte osmotic fragility analysis was carried out according to the method described by Hasegawa et al (2012). Briefly, erythrocytes were incubated in a series of NaCl concentrations ranging from 0.24% to 0.68%.…”
Section: Osmotic Fragility Test In Erythrocytesmentioning
confidence: 99%